Beyond Traditional Channels: A baseline data for Causal Assessment of Social Media's Impact on Smallholder Farmers' Practices in Isingiro district. - Katungi, Enid Mbabazi; Aseete, Paul; Ochieng, Justus; Mugaga Isaac; Babirye, Immaculate (2025)
This study aims to assess the causal impact of social media on smallholder farmers' knowledge and adoption of agricultural practices, comparing its effectiveness to traditional extension channels. It further identifies the mechanisms of this influence and the farmer profiles that benefit most, providing evidence for designing more efficient and scalable extension programs. A baseline survey was conducted and data collected from bean-growing farmers to establish the benchmarks of key outcome variables before the intervention. A baseline also provided insights into the context, and information used to select suitable varieties for dissemination and customize the information messages. Methodology:This study used a cluster-randomized controlled trial (cRCT) to compare how two different communication channels affect farmers' adoption of improved biofortified bean varieties. Sub counties were randomly assigned to one of three treatment arms: 1. Social Media Extension: Farmers received informational videos via social media. 2. Traditional Extension: Farmers attended in-person training with a local agent. 3. Control Group.